The Effect of Profitability, Operating cash flow, Economic Value Added and Firm Size on Stock Return - Roqijah, Ifa; Nugroho, Wawan Sadtyo; Nurcahyono, Nurcahyono (Universitas Muhammadiyah Semarang, 2022)
The return that investors will receive is one of the main factors in investment decisions. The higher the promised return, the more motivated investors will be in investing. This study aims to analyze the effect of ROA, OCF, EVA, and firm size on stock returns in manufacturing. The population of this study is manufacturing enterprise listed on the Indonesia stock exchange from 2018 to 2021, using the purposive sampling method. This research uses quantitative methods with data sources from the company's financial statements. The number of samples obtained was 125 companies. The analysis used is descriptive statistical analysis and multiple regression analysis. The results showed that return on assets, operating cash flow, economic value added, and company size were effective predictors in assessing the increase in stock returns in manufacturing enterprises during the study year. The implications of this research can be used in the development of stock return theory. Additionally, it can serve as a preference in the decision-making process for both investors and companies.